Diagnosis and management of benign secreting pancreatic insulinoma: What’s new? 4 case report - Khawla Bahou; Youssef Achour; Mehdi Ilahiane; Hamza Sekkat; Younes Bakali; Mouna Mhamdi Alaoui; Mohammed Raiss; Farid Sabbah; Abdelmalek Hrora (Rare Tumors)
Introduction and importance: Even though insulinoma is the most frequent neuroendocrine tumor, it represents only 2% of pancreatic 2% of all pancreatic neoplasms. Diagnosis is relatively simple, and surgery after accurate determination of the tumors location within the pancreas is the cornerstone of its treatment. Case presentation: We herein report 4 patients undergoing various surgeries for benign secreting insulinomas, after extensive radiological and endoscopic exploration. Clinical discussion: Diagnosis is relatively simple relying on clinical and biological criteria, it must be followed by an extensive and accurate preoperative determination of the tumors localization. The laparoscopic tumoral enucleation is the treatment of choice for small isolated tumors, but open surgery still has its indications. Conclusion: Pancreatic insulinoma is a rare neuroendocrine tumor that can be life-threatening due to hypoglycemic manifestations. The diagnosis is based on clinical and biological criteria. echo endoscopy and to a lesser extent radiological exploration can precisely determine the tumors location. Laparoscopic surgical enucleation of the tumor remains the preferred curative treatment.